2009
DOI: 10.1088/0022-3727/42/14/145111
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of temperature dependent dc current transport mechanism on Au/poly(4-vinyl phenol)/p-Si device

Abstract: In this study, temperature dependent current–voltage (I–V) measurements and investigation of the dc current transport mechanism of Au/poly(4-vinyl phenol)/p-Si device have been performed. While the series resistance value displayed nearly temperature independent behaviour, the ideality factor varied between 7.26 and 2.76 in the temperature range 100–300 K. There is a linear relationship between the barrier height and the ideality factor which is attributed to barrier height inhomogeneities in the Au/poly(4-vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Several reported that if n varies between 1 and 2, the tunneling current mechanism is dominant, if n=2, the generation recombination current mechanism is dominant and if n>2, the leakage current mechanism is dominant [35]. The values of n and I s are found to be ( [37].The barrier height  b can be calculated from the following relation:…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…Several reported that if n varies between 1 and 2, the tunneling current mechanism is dominant, if n=2, the generation recombination current mechanism is dominant and if n>2, the leakage current mechanism is dominant [35]. The values of n and I s are found to be ( [37].The barrier height  b can be calculated from the following relation:…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…In this technique, an organic interfacial layer is inserted between inorganic semiconductor and metal. As they can be applied to various areas like solar cells and Schottky diodes, there has been a growing interest in polymers such as poly(4-vinyl phenol), polyaniline, polyvinyl alcohol (PVA), poly(alkylthiophene) polypyrrole, polythiophene, and poly(3-hexylthiophene) [7][8][9][10][11][12][13][14][15][16][17][18]. In polymers, we find local free-volume holes or cavities of atomic and molecular dimensions, which may be the result of irregular packing of the molecules in amorphous phase (static and preexisting holes) and molecular relaxation of polymer chains and terminal ends (dynamic and transient holes).…”
Section: Introductionmentioning
confidence: 99%
“…[10] In the case of germanium, the different experimental observations tend to strengthened one or the other theory. [4,[11][12][13] However, in most of the case, possible SBHs non-homogeneities which can alter the electrical properties of real MS contacts [14][15][16][17] are not taken into account.…”
Section: Introductionmentioning
confidence: 99%